2021
DOI: 10.3390/microorganisms9122603
|View full text |Cite
|
Sign up to set email alerts
|

Several Yeast Species Induce Iron Deficiency Responses in Cucumber Plants (Cucumis sativus L.)

Abstract: Iron (Fe) deficiency is a first-order agronomic problem that causes a significant decrease in crop yield and quality. Paradoxically, Fe is very abundant in most soils, mainly in its oxidized form, but is poorly soluble and with low availability for plants. In order to alleviate this situation, plants develop different morphological and physiological Fe-deficiency responses, mainly in their roots, to facilitate Fe mobilization and acquisition. Even so, Fe fertilizers, mainly Fe chelates, are widely used in mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 62 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…Relative to the fungus species we found arbuscular mycorrhizal [ 87 , 88 ], Trichoderma asperellum and Trichoderma harzianum [ 89 , 90 ]. Recently, Lucena et al [ 91 ] found that two yeast strain, Debaromyces hansenii and Hansenula polymorpha were able to induce Fe deficiency responses in cucumber plants. However, any works relative to IPF as Fe deficiency responses inductor can be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the fungus species we found arbuscular mycorrhizal [ 87 , 88 ], Trichoderma asperellum and Trichoderma harzianum [ 89 , 90 ]. Recently, Lucena et al [ 91 ] found that two yeast strain, Debaromyces hansenii and Hansenula polymorpha were able to induce Fe deficiency responses in cucumber plants. However, any works relative to IPF as Fe deficiency responses inductor can be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we take a further step towards optimizing the use of yeasts as growth promoters and for enhancing plant nutrition. Although, both D. hansenii and H. polymorpha showed a remarkable ability to induce Fe deficiency responses, this study specifically Locally, some rhizosphere microorganisms can induce Fe deficiency responses, contributing to an improvement of plant nutrition and, as consequence, promoting plant growth and alleviating Fe chlorosis [1,2,10,11,26]. Created with BioRender.com.…”
Section: Introductionmentioning
confidence: 98%
“…Ashley) plants, such as ferric reductase activity and rhizosphere acidification, and to increase the expression of Fe acquisition genes, including FRO1 (ferric reductase oxidase 1), IRT1 (iron-regulated transporter 1), and HA1 (H + -ATPase 1). Furthermore, both D. hansenii and H. polymorpha fostered the development of subapical root hairs, a characteristic morphological response to Fe deficiency [2] (Figure 1). Locally, some rhizosphere microorganisms can induce Fe deficiency responses, contributing to an improvement of plant nutrition and, as consequence, promoting plant growth and alleviating Fe chlorosis [1,2,10,11,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad interest has been developed for this topic during the last years (e.g. Garcia et al, 2016;Guerrero-Galań et al, 2018;Garcia et al, 2020;Lucena et al, 2021b). In this context, the study by Shan et al dealing with the beneficial effects of mycorrhizal fungi for orchid growth is clearly demonstrating an improvement in nitrogen uptake.…”
mentioning
confidence: 99%